Hydrogen adsorption in ZIF-7: A DFT and ab-initio molecular dynamics study - Dixit, Mudit; Major, Dan Thomas; Pal, Sourav (Chemical Physics Letters, 2016)
Primary H-2 adsorption sites in a zeolitic imidazolate framework, ZIF-7, are identified using ab-initio density functional theory (DFT) based molecular dynamics annealing simulations. The simulations suggest several low energy adsorption sites. The effect of light transition metal decoration on hydrogen storage properties was studied. Our ab-intio DFT calculations illustrate that decorating the ZIF with Sc increases both the number of H-2 molecules, as well as the H-2 binding energy. The binding energy (similar to 25 kJ/mol per H-2) at 8H(2) loading in the pore, suggests that Sc-ZIFs can be potential candidates for hydrogen storage. (C) 2016 Elsevier B.V. All rights reserved.